Influence of CrossFit and Deep End Fitness training on mental health and coping in athletes - Cansler, Rachel; Heidrich, Jerome; Whiting, Ali; Tran, Don; Hall, Prime; Tyler, William J. (Frontiers in Sports and Active Living, 2023)
Physical exercise is known to improve mental health. Athletes can experience unique physical and emotional stressors, which can deteriorate mental health and cognitive function. Training apathy can lead to cognitive dissonance and further degrade performance by promoting maladaptive, avoidance coping strategies. Introduction of psychosocial and training variables, such as those used in CrossFit (CF) and other community-based fitness programs with strong peer support have been shown to help reduce training apathy and negative affect. Here, we explored whether addition of psychophysiological variation, experienced as “hunger for air” during underwater breath-hold exercises, could provide unique mental health benefits for athletes. We studied the influence of CF and Deep End Fitness (DEF), a community-based underwater fitness program, on several outcome measures of mental health and emotional well-being in volunteer athletes. We observed a significant reduction in stress scores of both the control CF training group and the experimental DEF group. We found that DEF produced a significant improvement in positive affect while CF training did not. Further supportive of our hypothesis that the psychological and biological stressors experienced in underwater, breath-hold training cause positive adaptive changes and benefits, DEF training uniquely increased problem-based coping. While our observations demonstrate both CF and DEF training can improve mental health in athletes, DEF produced additional, unique benefits to positive coping and attitudes of athletes. Future studies should further evaluate the broader benefits of community-based, underwater training programs on psychological and physiological health in athletes and the public.